PENGARUH IMPLEMENTASI METODE YANBU’A TERHADAP KETERAMPILAN BACA TULIS AL-QUR’AN PADA MATA PELAJARAN AL-QUR’AN SCIENCE KELAS X SMA DI PONDOK PESANTREN BAYT AL-HIKMAH PASURUAN - Nur Maiddah; Muhammad Fahmi Hidayatullah; Bahroin Budiya (VICRATINA, 2022)
The Yanbu'a method is a method of reading and writing the Qur'an which is arranged based on the level of learning that begins with knowing, reading, writing hijaiyah letters, and understanding the rules of reading the Qur'an properly and correctly. In the era of globalization which is also known as the development of the times, it is still found in various formal and non-formal institutions that use classical methods in the process of learning to read and write the Qur'an. The purpose of this study was to describe the level of effectiveness of the application of the yanbu'a method, to determine the level of efficiency in reading and writing the Qur'an and the effect of the yanbu'a method on the ability to read and write the Qur'an of class X students in the subjects of the Qur'an. Science at the Bayt Alhikmah Islamic Boarding School, Pasuruan. The type of research used is quantitative correlation research. The results of the hypothesis research show that the value of tcount > ttable, then Ha is accepted and Ho is rejected, which means that there is a significant influence between the yanbu'a method partially on reading and writing skills of the Qur'an.